Ritual Paka Di’a dalam Tradisi Kematian Masyarakat Manggarai sebagai Ruang Perjumpaan antara Budaya dan Gereja - Fernandes Fernando (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
The Paka Di’a ritual is one of the death traditions in Manggarai culture, rich in spiritual, social, and cultural meanings. This tradition functions as an act of honoring ancestral spirits, strengthening family bonds, and preserving local wisdom. This study aims to understand Paka Di’a as a space of encounter between local culture and the Catholic Church’s tradition through the perspective of inculturation, as well as to explore its significance for the faith life of Manggarai Catholic communities. The research employs a qualitative approach using interviews and documentation involving traditional leaders, religious figures, and local community members. The findings show that Paka Di’a contains values that resonate with Catholic teachings, such as belief in life after death, prayers for the deceased, sacrifice, solidarity, and communal togetherness, manifested in the integration of traditional prayers with liturgical prayers and in communal acts of solidarity. This encounter demonstrates how local traditions can become a medium that enriches expressions of faith and broadens the community’s understanding of the relationship between culture and the Church. Thus, Paka Di’a serves not only as a means of preserving Manggarai cultural identity but also as a medium of inculturation that strengthens and enriches the faith life of Catholic believers in the Manggarai context.